(untitled) (Journal of the College of Basic Education, 2022)
A study was carried out to analysis of some heavy metals in nine different types of vinegar, belong to Grape, Apple, Synthetic White, Date, Hawthorn, Garlic, Cactus, Pomegranate and Ginger vinegar, which are locally available in Iraqi folk medicine markets. The concentrations of heavy metals in the studied samples including, Cr, Mg, Mn, Zn, Fe, Cd, Ni, Pb and Ag, were determining by using flame atomic absorption spectrophotometry. All data were subjected to statistical analysis by calculating accuracy, precision and correlation coefficient for each concentrations level. The results indicate that Ni was recorded the highest concentration in all studied samples except, Ginger and cactus vinegar, each one receded the highest concentration value of Mn(8.520µg.mL-1) and Fe (3.500µg.mL-1) respectively. Also it can be noticed that Ni shows the highest total concentration value (26.250µg.mL-1), while Cr recorded the lowest total concentration value (0.347µg.mL-1). The concentrations of each metal studied were in the limits of health intake and not considered a health risk.